1992
DOI: 10.1007/bf00918152
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of heterogeneous lymphokine-activated killer (LAK) receptors on Kaposi's sarcoma cells, endothelial cells, and monocytes/macrophages: Evidence of distinct LAK-cell antigen on Kaposi's sarcoma cells?Potential for use of LAK cells for immunotherapy

Abstract: The purpose of this study was to determine the potential use of lymphokine-activated killer (LAK) cells against Kaposi's sarcoma (KS) cells. We used chromium release cold-target inhibition assay for understanding the expression of heterogeneous LAK-cell antigens (Ags) on KS cells, endothelial cells (ECs), and monocytes/macrophages (M phi) which could allow for the utilization of LAK-cell immunotherapy in KS without side effects. Our data show that (i) all three cell types express the CD18 Ag of LFA-1 or Leu-CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Our results herein showed that although RH1-38 did not inhibit killing of AIDS-KS21 cells, it concomitantly inhibited rupture of AIDS-KS10 cells, vascular ECs and MΦ (Table 1). Combining this finding with our previous data, where AIDS-KS21 cells failed to cold-target inhibit lysis of vascular ECs, as otherwise demonstrated by AIDS-KS10 cells [10], summarize that AIDS-KS21 cells bore either diminished or negative CD54 Ag composition. Published papers to date have reported CD54 Ags on several other AIDS-KS cell lines unaffected following multiple passages in vitro [14], and that no significant immunophenotyping differences exist between AIDS-KS3, -KS6 and -KS8 cells at comparable stages [15].…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Our results herein showed that although RH1-38 did not inhibit killing of AIDS-KS21 cells, it concomitantly inhibited rupture of AIDS-KS10 cells, vascular ECs and MΦ (Table 1). Combining this finding with our previous data, where AIDS-KS21 cells failed to cold-target inhibit lysis of vascular ECs, as otherwise demonstrated by AIDS-KS10 cells [10], summarize that AIDS-KS21 cells bore either diminished or negative CD54 Ag composition. Published papers to date have reported CD54 Ags on several other AIDS-KS cell lines unaffected following multiple passages in vitro [14], and that no significant immunophenotyping differences exist between AIDS-KS3, -KS6 and -KS8 cells at comparable stages [15].…”
Section: Resultssupporting
confidence: 88%
“…In our earlier paper, we specified that AIDS-KS21 cells originated from an eye lesion, whereas, AIDS-KS10, -KS8 and -KS3 cells were cutaneous, visceral and pleural fluid isolates, respectively [10]. Juxtaposed was put the observation that the differences in reactions of AIDS-KS21 cells may be related to location, however, a plausible explanation could not be proposed [10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations